Surgery in Uremic Patients (Springer Nature, 2025)
This open access book on Surgery in Uremic Patients is a comprehensive guide for general surgeons about the management of the most prevalent surgical challenges and procedures in patients with renalfailure. It covers preoperative assessment, anesthetic considerations, postoperative care, and specialized procedures. The book emphasizes understanding uremia's impact on organ systems for informed decision-making. It discusses anesthetic strategies tailored to uremic patients, postoperative complications, and preventive measures like managing infections and fluid imbalances. Specialized procedures such as dialysis access surgery are detailed, along with integrating technology into modern surgical practices. Common surgeries like appendectomy, hernia repair, and cholecystectomy are optimized to minimize complications. Upper and lower gastrointestinal surgeries, hepatobiliary surgery, urological surgery, transplant surgery, endocrinosurgery, bariatric surgery, geriatric surgery, and abdominal emergencies are thoroughly covered. The book concludes with key findings, clinical implications, and future research avenues, serving as a valuable resource for surgeons and students enhancing their approach to uremic patient care.